1984
DOI: 10.1111/j.1365-2389.1984.tb00609.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil pH and high urea concentrations on urease activity in soil

Abstract: The rate of hydrolysis of urea in soil over the wide range of concentrations, up to 10 moles N per dm3 soil solution, found in fertilizer practice, was examined in Begbroke sandy loam adjusted to different p H values.On rewetting air-dry soil, urease activity increased rapidly, reached a maximum within the first 24 h and then decreased slowly to level off after about 4 days. Pretreatment of the soil with urea or ammonium had n o effect on the urease activity. Urease activity increased with substrate concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 15 publications
5
31
1
2
Order By: Relevance
“…Hydrolysis rate ( / U t ∂ ∂ ) increases first and then decreases with the increase in urea concentration [23] , which is different from this study's result. This study showed that hydrolysis rate ( / U t ∂ ∂ ) enhanced with the increase in urea concentration.…”
Section: Kinetics Of Urea Hydrolysis Under Different Treatmentscontrasting
confidence: 99%
See 2 more Smart Citations
“…Hydrolysis rate ( / U t ∂ ∂ ) increases first and then decreases with the increase in urea concentration [23] , which is different from this study's result. This study showed that hydrolysis rate ( / U t ∂ ∂ ) enhanced with the increase in urea concentration.…”
Section: Kinetics Of Urea Hydrolysis Under Different Treatmentscontrasting
confidence: 99%
“…Singh's report [23] , the moisture content was 50% and nitrogen application rate was less than 200 mg/kg. However, the moisture content was between 19.2% (60% of field capacities) and 32% (100% of field capacities) and nitrogen application rate was between 247 mg/kg and 433 mg/kg in this study.…”
Section: Kinetics Of Urea Hydrolysis Under Different Treatmentsmentioning
confidence: 89%
See 1 more Smart Citation
“…Santos et al (1991) observaram aumento na taxa de hidrólise da U com o incremento na concentração do fertilizante, porém não proporcional às doses avaliadas. Nessa reação, há consumo de H + do meio, elevando, conseqüentemente, o pH, o que favorece a volatilização de NH 3 , principalmente com o aumento das doses de U (Singh & Nye, 1984;Kiehl, 1989). As menores perdas por volatilização ocorreram nas fontes NA e SA (Quadro 1).…”
Section: Resultsunclassified
“…The rate of hydrolysis of urea is increased with an increase in urea concentrations until a maximum is reached, beyond which hydrolysis is decreased. The results can be explained by substrate inhibition at higher urea concentrations [43,44]. Pervin et al has also studied the effect of various metal ions and chemicals on the activity of chickpea urease.…”
Section: 4mentioning
confidence: 99%